An illusion of exoticism: The evolution of the perception of Africa in Poland (1945-1989) - Popławski, Błażej (Journal of Central and Eastern European African Studies, 2024)
The aim of this article is to describe the evolution of the perception of Africa, especially the Sub-Saharan part, and its inhabitants in Poland between 1945 and 1989 on the basis of official documents, literary sources, and memoirs. It is possible to assume that the process of conventionalization of the symbols generated the image of the “Dark Continent” and the substantial modification of the language of cognition – from “Afro-Optimistic” in the early 1960s to “Afro-Pessimistic” in the 1980s. This change was caused by various factors: cold-war geopolitics, anticolonial and “fraternal aid” rhetoric, frequency of social interaction, more visible presence of Africans in the cultural landscape of Poland, and liberalization in terms of “passport politics” in the People’s Republic of Poland (in Polish: Polska Rzeczpospolita Ludowa, PRL).